APPLYING VIDEO-STIMULATED REFLECTION AS A LEARNING STRATEGY TO ENHANCE EFL STUDENTS' SPEAKING PERFORMANCE - Dian Safitri; Ferawati Ferawati; Herri Mulyono (Universitas Muhammadiyah Tangerang, 2021)
This qualitative study aimed to examine video-stimulated reflection as a learning strategy to enhance English as a foreign language (EFL) students' speaking performance. The data from six students majoring in English Education, in a private university in Indonesia were collected through students' reflection journals and semi-structured interviews. The results were analyzed using thematic analysis. The findings of the current study indicate that video-stimulated reflection has encouraged students to improve their speaking ability. More specifically, the key targets for enhancing the performance of students' in speaking to others on a daily basis were voice control, body language, and effectiveness.